Competition functions and productivity in sugarcane-based associative and successive cropping systems in relation to nitrogen and sulphur nutrition - SHUKLA, S K; MENHILAL, MENHILAL (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1996-98 and 1997-99 at Lucknow with 3 crpping systems, viz autumn sugarcane (sole), autumn cane + indian mustard [Brassica juncea (L.) Czernj. & Cosson] in 1:1 row ratio and indian mustardsugarcane, at 3 levels each of nitrogen (150, 225 and 300 kg N/ha) and sulphar (0,30 and 60kg S/ha) to optimize N and S fertilizer schedule for a cropping system as a whole. An intercropping of indian mustard with autumn sugarcane increased cane-equivalent yield (118.5 tonnes/haÂ  or 263.07 kg/ha/day). Increaseing nitrogen (150-300 kg N/ha) and sulphar doses(0-60 kg S/ha) for whole cropping system individually increased came nitrogen 84.62-94.30 tonnes/ha and sulphur 77.44-101.94 tonnes/ha) and cane-equivalent yield (N 112.95-130.07 and S 109.07-137.96 tonnes/ha). Nitrogen and sulphur could not influence juice quality (brix, pol and purity). Land-equivalent ratio (N 1.69-1.73 and S 1.67-1.74) increased with increasing nitrogen and sulphur levels.